Private Trust under Ethiopian Law: Constitution, Nature and Administration - Abate, Yibekal Tadesse (Bahir Dar University Journal of Law, 2022)
A trust can be constituted for private interest as a private trust or for the public benefit as a charitable trust. Until Ethiopia promulgated a proclamation governing Charities and Societies in 2009, trusts had been primarily regulated under Ethiopian Civil Code of 1960. The Civil Code provides the legal regime for trusts recognizing, inter alia, that a person can establish trust for the benefit of any person, idea, or action. This shows that the Code has envisaged that a trust can be constituted as a private or charitable trust. However, currently, while charitable trusts are mainly governed under the Organization of Civil Societies Proclamation, private trusts remain under the ambit of the Civil Code. Given the fact that private trusts are not commonly known in Ethiopia, it is important to examine questions surrounding the nature of such institutions and how they are to be regulated in Ethiopia. The aim of the Article is, therefore, to elucidate the nature, purpose, formation and administration of these institutions in this country. To this end, doctrinal legal research approach is employed in the course of which pertinent legislations and literature have been explored, analysed and synthesized. The researchfound out, in the context of Ethiopian trust law, the feature and purpose of private trust is different from other comparable legal relationships such as agency, third party beneficiary contract, testate succession and bailment. The trustee is a major player while other parties such as the trust maker, beneficiaries, courts and the General Attorneys could be involved in the administration of trust.